Nationwide surveillance of the antimicrobial susceptibility of Chlamydia trachomatis from male urethritis in Japan: Comparison with the first surveillance report. Issue 1 (January 2022) - Takahashi, Satoshi; Yasuda, Mitsuru; Wada, Koichiro; Matsumoto, Masahiro; Hayami, Hiroshi; Kobayashi, Kanao; Miyazaki, Jun; Kiyota, Hiroshi; Matsumoto, Tetsuya; Yotsuyanagi, Hiroshi; Tateda, Kazuhiro; Sato, Junko; et al.
Abstract: The Urogenital Sub-committee and the Surveillance Committee of the Japanese Society of Chemotherapy, The Japanese Association for Infectious Diseases, and the Japanese Society for Clinical Microbiology conducted the second nationwide surveillance of the antimicrobial susceptibility of Chlamydia trachomatis . In this second surveillance study, clinical urethral discharge specimens were collected from patients with urethritis in 26 hospitals and clinics from May 2016 to July 2017. Based on serial cultures, the minimum inhibitory concentration (MIC) could be determined for 41 isolates; the MICs (MIC90 ) of ciprofloxacin, levofloxacin, tosufloxacin, sitafloxacin, doxycycline, minocycline, erythromycin, clarithromycin, azithromycin and solithromycin were 2 μg/ml (2 μg/ml), 1 μg/ml (0.5 μg/ml), 0.25 μg/ml (0.25 μg/ml), 0.125 μg/ml (0.063 μg/ml), 0.125 μg/ml (0.125 μg/ml), 0.25 μg/ml (0.25 μg/ml), 0.031 μg/ml (0.031 μg/ml), 0.25 μg/ml (0.125 μg/ml), and 0.016 μg/ml (0.008 μg/ml), respectively. In summary, this surveillance project did not identify any strains resistant to fluoroquinolone, tetracycline, or macrolide agents in Japan. In addition, the MIC of solithromycin was favorable and lower than that of other antimicrobial agents. However, the MIC of azithromycin had a slightly higher value than that reported in the first surveillance report, though this might be within the acceptable margin of error. Therefore, the susceptibility of azithromycin, especially, should be monitored henceforth.